Calcar buttressed screw fixation for femoral neck fracture - Manoj, K. K. Arvind; Karthik, R.; Sankar, A. Vishnu (International Journal of Research in Orthopaedics, 2018)
Background: The incidence of neck of femur fracture among elderly population is increasing day by day. Femoral neck fracture has always been an unsolved fracture as far as treatment and results are concerned. There are different views regarding the optimal method of internal ﬁxation in femoral neck fractures. Biomechanical data from literature suggest that calcar ﬁxation is superior to central screws placement. This study aims to analyse the functional and radiological outcome of femoral neck fractures treated by calcar buttressed screw fixation described by Filipov as biplane double supported screw fixation. Methods: This is a prospective study conducted in our institution from May 2015 to May 2018.The study included 43 patients (31 male, 12 female) with femoral neck fracture. Three 6.5-mm cannulated screws were laid in two medially diverging oblique planes. The distal and the middle screws were supported on the calcar. The distal screw had additional support on the posterior neck cortex. Patients were followed up for average period of 2 years. Functional outcome was evaluated using Harris Hip score. Results: Bone union occurred in 40 patients (93%) with average period of 3-4 months. 51.2% of cases had excellent outcome. 23.2% of cases had good and 16.3% of cases had fair outcome. 9.3% of cases ended with poor outcome. Non union was reported in 3 patients (7%) and AVN in one patient. Various factors like age, Garden and Pauwel fracture types, time of presentation and time of surgery were statistically significant to the final functional outcome in our study. Conclusions: By providing additional calcar buttress compared to conventional method, this technique of screw fixation enhances femoral neck fracture fixation strength and reduces the fixation failure.